High-reflectivity polycarbonate composite material as well as preparation method and application thereof

By adding titanium dioxide, barium sulfate, modified silane and coupling agent to the polycarbonate material, the proportion and physical properties parameters of each component are regulated, and the problem of insufficient performance of high reflectivity polycarbonate materials in the prior art is solved, and the comprehensive improvement of high reflectivity, gloss and wear resistance is achieved. It is suitable for a variety of optical devices.

CN119775750APending Publication Date: 2025-04-08SHANGHAI ZHONGLEI NEW MATERIAL SCI CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411982064.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

It is difficult to develop polymer polycarbonate materials with higher reflectivity in the prior art, and cannot meet the special requirements for optical performance in different industries.

Method used

By combining polycarbonate, titanium dioxide, barium sulfate, modified silane and coupling agent, the proportion and physical properties of each component are regulated, and a high reflectivity polycarbonate composite material is prepared. Titanium dioxide improves reflectivity and wear resistance, barium sulfate and modified silane reinforced materials gloss and mechanical properties, and coupling agent improves the dispersion and bonding strength of titanium dioxide.

Benefits of technology

It has achieved high reflectivity (reflectivity up to more than 95%), high gloss, good texture and good wear resistance of polycarbonate composite materials, and is suitable for different optical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221768100000021
    Figure BDA0005221768100000021
  • Figure BDA0005221768100000081
    Figure BDA0005221768100000081
  • Figure BDA0005221768100000091
    Figure BDA0005221768100000091
Patent Text Reader

Abstract

The invention provides a high-reflectivity polycarbonate composite material as well as a preparation method and application thereof. The high-reflectivity polycarbonate composite material is prepared from the following components in parts by weight: 80 to 90 parts of polycarbonate, 8 to 10 parts of titanium dioxide, 5 to 8 parts of barium sulfate, 0.5 to 1 part of modified silane and 0.1 to 1 part of coupling agent. The polycarbonate composite material provided by the invention not only has the characteristics of good texture, high gloss and high reflectivity, but also has good wear resistance and shading property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer modified materials, and in particular relates to a high-reflectivity polycarbonate composite material and a preparation method and application thereof. Background Art

[0002] High reflectivity materials refer to materials with high reflectivity. Reflectivity refers to the ratio of the intensity of light reflected from the surface of the material to the intensity of the incident light. High reflectivity materials are widely used in optical devices, including automotive headlight covers, ambient light brackets, reflectors, mirrors, gratings, and filters. It can be seen that high reflectivity materials have important application value in optical devices, and the improvement of their optical performance is the key to realizing these applications.

[0003] Among them, polycarbonate materials occupy an extremely important position in the field of optical lenses due to their unique characteristics of high light transmittance, high refractive index, high impact resistance, dimensional stability and easy processing and molding. Optical lenses made of optical grade polycarbonate can be used not only in cameras, microscopes, telescopes and optical testing instruments, but also in movie projector lenses, copier lenses, infrared automatic focus projector lenses, laser beam printer lenses, various prisms, multi-faceted reflectors and many other office equipment and home appliances. Its application market is extremely broad. At present, the market demand for high reflectivity polycarbonate materials is relatively large, but it is difficult to obtain materials with higher reflectivity with existing technologies.

[0004] Therefore, there is an urgent need to develop a polycarbonate material with high reflectivity to meet the special requirements of different industries for optical properties. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a high-reflectivity polycarbonate composite material and its preparation method and application. The polycarbonate composite material provided by the present invention not only has the characteristics of good texture, high gloss and high reflectivity, but also has good wear resistance and light-shielding properties.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a high reflectivity polycarbonate composite material, wherein the high reflectivity polycarbonate composite material comprises the following components in parts by weight:

[0008]

[0009] It should be noted that the high reflectivity refers to the reflectivity of the polycarbonate composite material being as high as 95% or more.

[0010] The high reflectivity polycarbonate composite material provided by the present invention comprises a combination of polycarbonate, titanium dioxide, barium sulfate, modified silane and coupling agent; wherein titanium dioxide is an inorganic pigment with high whiteness, strong hiding power and good optical properties, and these properties enable titanium dioxide to effectively reflect light, not only to provide a bright porcelain white appearance, but also to increase the reflectivity of the material surface to light, so that the gloss of the polycarbonate composite material is improved. At the same time, the addition of titanium dioxide can also improve the wear resistance of the polycarbonate composite material, so that the product has more mechanical strength, thereby extending the service life of the polycarbonate composite material; in addition, the modified silane can improve the interface performance of barium sulfate, thereby improving the fluidity and gloss of the material, and the combined use of barium sulfate and modified silane can not only improve the surface gloss of the polycarbonate composite material, but also enhance its strength, chemical corrosion resistance and weather resistance; finally, the coupling agent reacts chemically with the trace hydroxyl or proton adsorbed on the surface of titanium dioxide through the active group, and forms a monolayer on the surface of titanium dioxide, thereby improving the dispersibility and bonding strength of titanium dioxide in polycarbonate.

[0011] The polycarbonate composite material of the present invention has the advantages of high reflectivity, high gloss, good texture and good wear resistance through the screening and compounding of components, so it is suitable for different optical devices.

[0012] In the present invention, the weight proportion of the polycarbonate is 80-90 parts, for example, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, etc.

[0013] In the present invention, the weight percentage of the titanium dioxide is 8-10 parts, for example, 8 parts, 8.2 parts, 8.5 parts, 8.8 parts, 9 parts, 9.2 parts, 9.5 parts, 9.8 parts, 10 parts, etc. If the weight percentage of the titanium dioxide is higher, the impact performance of the prepared polycarbonate composite material will be reduced.

[0014] In the present invention, the weight percentage of the barium sulfate is 5-8 parts, for example, 5 parts, 5.2 parts, 5.5 parts, 5.8 parts, 6 parts, 6.2 parts, 6.5 parts, 6.8 parts, 7 parts, 7.2 parts, 7.5 parts, 7.8 parts, 8 parts, etc. If the weight percentage of the barium sulfate is higher, the impact performance of the prepared polycarbonate composite material will be reduced.

[0015] In the present invention, the weight percentage of the modified silane is 0.5-1 part, for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc. If the weight percentage of the modified silane is low, the gloss and reflectivity of the prepared polycarbonate composite material will be reduced; if the weight percentage of the modified silane is high, the impact performance of the prepared polycarbonate composite material will be reduced.

[0016] In the present invention, the mass percentage of the coupling agent is 0.1 part to 1 part, for example, it can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc.

[0017] Preferably, the weight average molecular weight of the polycarbonate is 40,000.

[0018] Preferably, the titanium dioxide is selected from rutile type titanium dioxide with a titanium dioxide content greater than 97%.

[0019] Preferably, the whiteness of the titanium dioxide is 98.

[0020] Preferably, the density of the titanium dioxide is 4.2 g / cm 3 -4.3g / cm 3 , for example, it can be 4.2 g / cm 3 4.22g / cm 3 4.25g / cm 3 4.28g / cm 3 , 4.3g / cm 3 wait.

[0021] Preferably, the oil absorption of the titanium dioxide is 15-18, for example, 15, 16, 17, 18, etc.

[0022] Preferably, the titanium dioxide passes through a 325-mesh sieve, and the content of the residue is less than 0.01%.

[0023] In the present invention, the glossiness and reflectivity of the polycarbonate composite material are improved by adjusting the above physical property parameters of titanium dioxide.

[0024] Preferably, the barium sulfate is precipitated barium sulfate.

[0025] Preferably, the whiteness of the barium sulfate is 98.

[0026] Preferably, the specific gravity of the barium sulfate is 4.0-4.6, for example, it can be 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, etc.

[0027] Preferably, the oil absorption of the barium sulfate is 13-18, for example, it can be 13, 14, 15, 16, 17, 18, etc.

[0028] Preferably, the barium sulfate passes through a 325-mesh sieve, and the content of the residue is less than 0.01%.

[0029] In the present invention, the whiteness, glossiness and mechanical properties of the polycarbonate composite material are improved by regulating the above physical parameters of barium sulfate.

[0030] Preferably, the modified silane is an amino-modified silane compound. Modified silane is an organic silicon compound having advantages such as good weather resistance, water resistance, chemical corrosion resistance and electrical insulation performance.

[0031] Preferably, the amino-modified silane compound includes a polyurethane-modified silane compound. The present invention introduces a polyurethane structural unit into the structure of the silane compound, so that the modified silane not only retains its excellent aging resistance, but also has good adhesion and strength, and combines the performance advantages of the two, ultimately improving not only the interface performance of titanium dioxide, but also the fluidity and gloss of the polycarbonate composite material.

[0032] Preferably, the weight average molecular weight of the polyurethane-modified silane compound is 350.

[0033] Preferably, the high reflectivity polycarbonate composite material further comprises, by weight: 0.01 to 0.1 parts of pigment, 0.1 to 0.5 parts of fluorescent brightener, and 0.1 to 1 parts of other additives.

[0034] In the present invention, the weight percentage of the pigment is 0.01-1 part, for example, it can be 0.01 part, 0.02 part, 0.05 part, 0.08 part, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc. If the weight percentage of the pigment is low, the whiteness of the prepared polycarbonate composite material will be reduced, and the reflectivity will be reduced accordingly; if the weight percentage of the pigment is high, the whiteness of the prepared polycarbonate composite material will be reduced, and the reflectivity will also be reduced.

[0035] In the present invention, the weight percentage of the fluorescent whitening agent is 0.1-0.5 parts, for example, it can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, etc. The addition of the fluorescent whitening agent is to improve the whiteness of the polycarbonate composite material, and secondly, the fluorescent whitening agent itself is a material with high reflectivity, thereby further improving the whiteness and reflectivity of the composite material.

[0036] In the present invention, the weight proportion of the other auxiliary agents is 0.1-1 part, for example, it can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc.

[0037] Preferably, the pigment includes ultramarine blue. The present invention eliminates the yellow light of the base color of the polycarbonate composite material by adding ultramarine blue pigment, so that the reflective effect is better.

[0038] Preferably, the other auxiliary agent includes at least one of a heat stabilizer, an antioxidant or a dispersant. The heat stabilizer, antioxidant and dispersant can be any conventional type in the art, and the present invention does not limit this.

[0039] In a second aspect, the present invention provides a method for preparing the high reflectivity polycarbonate composite material according to the first aspect, the method comprising the following steps:

[0040] Polycarbonate, titanium dioxide, barium sulfate, modified silane and coupling agent are mixed according to the formula to obtain a mixture; the mixture is extruded to obtain the high-reflectivity polycarbonate composite material.

[0041] Preferably, the extrusion equipment is a twin-screw extruder.

[0042] Preferably, the extrusion adopts sequential zone heating: the heating temperature of the first heating zone is 180°C-220°C (for example, it can be 180°C, 190°C, 200°C, 210°C, 220°C, etc.), the heating temperature of the second heating zone is 190°C-230°C (for example, it can be 190°C, 200°C, 210°C, 220°C, 230°C, etc.), the heating temperature of the third heating zone is 200°C-250°C (for example, it can be 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc.), the heating temperature of the fourth heating zone is 200°C-250°C (for example, it can be 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc.), and the heating temperature of the fifth heating zone is 200°C-250°C (for example, it can be The heating temperature of the sixth heating zone is 200℃-250℃ (for example, it can be 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, etc.), the heating temperature of the seventh heating zone is 200℃-250℃ (for example, it can be 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, etc.), the heating temperature of the eighth heating zone is 200℃-250℃ (for example, it can be 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, etc.), and the heating temperature of the ninth heating zone is 200℃-250℃ (for example, it can be 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, etc.).

[0043] Preferably, the temperature of the head of the twin-screw extruder is 190°C-240°C, for example, it can be 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, etc.; the speed of the main engine is 300r / min-500r / min, for example, it can be 300r / min, 320r / min, 350r / min, 380r / min, 400r / min, 420r / min, 450r / min, 480r / min, 500r / min, etc.

[0044] In the present invention, pelletizing is performed after the extrusion.

[0045] In a third aspect, the present invention provides a use of the high-reflectivity polycarbonate composite material according to the first aspect, wherein the high-reflectivity polycarbonate composite material is used to make reflective cups / covers of lighting fixtures, instruments or meters.

[0046] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The invention provides a high-reflectivity polycarbonate composite material, which comprises a combination of polycarbonate, titanium dioxide, barium sulfate, modified silane and a coupling agent; wherein the titanium dioxide is an inorganic pigment with high whiteness, strong hiding power and good optical properties, and these properties enable the titanium dioxide to effectively reflect light, not only to provide a bright porcelain white appearance, but also to increase the reflectivity of the material surface to light, thereby improving the gloss of the polycarbonate composite material. At the same time, the addition of titanium dioxide can also improve the wear resistance of polycarbonate composites, make the products more mechanically strong, and thus extend the service life of polycarbonate composites; in addition, modified silane can improve the interfacial properties of barium sulfate, thereby improving the fluidity and gloss of the material, and the combination of barium sulfate and modified silane can not only improve the surface gloss of polycarbonate composites, but also enhance its strength, chemical corrosion resistance and weather resistance; finally, the coupling agent reacts chemically with trace hydroxyl groups or protons adsorbed on the surface of titanium dioxide through active groups to form a monomolecular layer on the surface of titanium dioxide, thereby improving the dispersibility and bonding strength of titanium dioxide in polycarbonate.

[0049] The polycarbonate composite material of the present invention has the advantages of high reflectivity, high gloss, good texture and good wear resistance through the screening and compounding of components, so it is suitable for different optical devices.

[0050] The polycarbonate composite material of the present invention has low production cost and is suitable for batch preparation. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0052] Example 1

[0053] This embodiment provides a high reflectivity polycarbonate composite material, which includes the following components in parts by weight:

[0054]

[0055]

[0056] Among them, the weight average molecular weight of polycarbonate is 40,000; the titanium dioxide content in rutile titanium dioxide is greater than 97%, the whiteness is 98, and the density is 4.25g / cm 3 , oil absorption is 16, and it passes through a 325-mesh sieve with a sieve residue content of less than 0.01%; the whiteness of the precipitated barium sulfate is 98, the specific gravity is 4.3, the oil absorption is 15, and it passes through a 325-mesh sieve with a sieve residue content of less than 0.01%; the weight-average molecular weight of the polyurethane-modified silane is 350; the fluorescent whitening agent is 4,4'-di(benzoxazole-2-yl)trans-diphenylethylene, the coupling agent is silane coupling agent KH-570; the thermal stabilizer is hindered phenol antioxidant 1010.

[0057] This embodiment also provides a method for preparing the above-mentioned high reflectivity polycarbonate composite material, which comprises the following steps:

[0058] Polycarbonate, rutile titanium dioxide, precipitated barium sulfate, polyurethane-modified silane, ultramarine, fluorescent brightener, coupling agent and thermal stabilizer are mixed according to the formula to obtain a mixture; the mixture is extruded by a twin-screw extruder, and pelletized to obtain the high-reflectivity polycarbonate composite material;

[0059] Specifically, the extrusion process adopts sequential zone heating: the heating temperature of the first heating zone is 200°C, the heating temperature of the second heating zone is 210°C, the heating temperature of the third heating zone is 220°C, the heating temperature of the fourth heating zone is 220°C, the heating temperature of the fifth heating zone is 220°C, the heating temperature of the sixth heating zone is 220°C, the heating temperature of the seventh heating zone is 220°C, the heating temperature of the eighth heating zone is 220°C, and the heating temperature of the ninth heating zone is 220°C; the temperature of the head of the twin-screw extruder is 230°C, and the speed of the main engine is 400r / min.

[0060] Comparative Example 1

[0061] The difference between this comparative example and Example 1 is that precipitated barium sulfate is not added, and the other aspects are the same as Example 1.

[0062] Comparative Example 2

[0063] The difference between this comparative example and Example 1 is that ultramarine is not added, and the other aspects are the same as Example 1.

[0064] Comparative Example 3

[0065] The difference between this comparative example and Example 1 is that no polyurethane-modified silane is added, and the other aspects are the same as Example 1.

[0066] Comparative Example 4

[0067] The difference between this comparative example and Example 1 is that no 4,4'-di(benzoxazole-2-yl) trans-stilbene fluorescent whitening agent is added, and the other contents are the same as those in Example 1.

[0068] Test conditions

[0069] The polycarbonate composite materials provided in Example 1 and Comparative Examples 1 to 4 were subjected to performance tests, and the test methods are as follows:

[0070] Light reflectivity: tested in accordance with DIN 5033.

[0071] The test results are shown in Table 1:

[0072] Table 1

[0073]

[0074]

[0075] As can be seen from the table, the present invention adjusts the specific composition of the polycarbonate composite material, further optimizes the types of components and their weight fractions, and utilizes the screening and compounding of the components to make it have the advantages of high reflectivity, high gloss, good texture and good wear resistance, which is specifically manifested in a reflectivity of up to 98%, so that it is suitable for different optical devices.

[0076] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high reflectivity polycarbonate composite material, characterized in that: The high reflectivity polycarbonate composite material comprises the following components in parts by weight:

2. The high reflectivity polycarbonate composite material according to claim 1, characterized in that: The weight average molecular weight of the polycarbonate is 40,000.

3. The high reflectivity polycarbonate composite material according to claim 1 or 2, wherein the titanium dioxide is selected from rutile type titanium dioxide with a titanium dioxide content greater than 97%.

4. The high reflectivity polycarbonate composite material according to any one of claims 1 to 3, characterized in that: The whiteness of the titanium dioxide is 98; Preferably, the density of the titanium dioxide is 4.2 g / cm 3 -4.3g / cm 3 ; Preferably, the oil absorption of the titanium dioxide is 15-18; Preferably, the titanium dioxide passes through a 325-mesh sieve, and the content of the residue is less than 0.01%.

5. The high reflectivity polycarbonate composite material according to any one of claims 1 to 4, characterized in that: The barium sulfate is precipitated barium sulfate; Preferably, the whiteness of the barium sulfate is 98; Preferably, the specific gravity of the barium sulfate is 4.0-4.6; Preferably, the oil absorption of the barium sulfate is 13-18; Preferably, the barium sulfate passes through a 325-mesh sieve, and the content of the residue is less than 0.01%.

6. The high reflectivity polycarbonate composite material according to any one of claims 1 to 5, characterized in that: The modified silane is an amino-modified silane compound; Preferably, the amino-modified silane compound comprises a polyurethane-modified silane compound; Preferably, the weight average molecular weight of the polyurethane-modified silane compound is 350.

7. The high reflectivity polycarbonate composite material according to any one of claims 1 to 6, characterized in that: In terms of weight, the high reflectivity polycarbonate composite material further comprises: 0.01 to 0.1 parts of pigment, 0.1 to 0.5 parts of fluorescent brightener, and 0.1 to 1 parts of other additives; Preferably, the pigment comprises Ultramarine Blue; Preferably, the other auxiliary agents include at least one of a heat stabilizer, an antioxidant or a dispersant.

8. A method for preparing a high reflectivity polycarbonate composite material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: Polycarbonate, titanium dioxide, barium sulfate, modified silane and coupling agent are mixed according to the formula to obtain a mixture; the mixture is extruded to obtain the high-reflectivity polycarbonate composite material.

9. The method according to claim 8, characterized in that The extrusion equipment is a twin-screw extruder; Preferably, the extrusion adopts sequential zone heating: the heating temperature of the first heating zone is 180°C-220°C, the heating temperature of the second heating zone is 190°C-230°C, the heating temperature of the third heating zone is 200°C-250°C, the heating temperature of the fourth heating zone is 200°C-250°C, the heating temperature of the fifth heating zone is 200°C-250°C, the heating temperature of the sixth heating zone is 200°C-250°C, the heating temperature of the seventh heating zone is 200°C-250°C, the heating temperature of the eighth heating zone is 200°C-250°C, and the heating temperature of the ninth heating zone is 200°C-250°C; Preferably, the temperature of the head of the twin-screw extruder is 190° C.-240° C., and the rotation speed of the main engine is 300 r / min-500 r / min.

10. An application of a high reflectivity polycarbonate composite material according to any one of claims 1 to 7, characterized in that: The high-reflectivity polycarbonate composite material is used for making reflective cups / covers of lighting fixtures, instruments or meters.

Citation Information

Patent Citations

  • Polycarbonate filled composite material

    CN102363668A

  • Imitated ceramic ultrahigh-wear-resistance polycarbonate resin and preparation method thereof

    CN112608588A

  • Single-component waterborne polyurethane waterproof coating and preparation method thereof

    CN113105814A

  • Polycarbonate resin composition and light-reflecting member

    JP2008195818A

  • Barium sulfate-containing composite

    US20090318594A1